2016
DOI: 10.1177/0886260516660973
|View full text |Cite
|
Sign up to set email alerts
|

Use of Health Services by Maltreated Children in Two Different Sociocultural Contexts: Where Can Doors for Interventions Be Opened?

Abstract: Among maltreated children, elevated use of non-routine (for illness or injury) services may coexist with underutilization of preventive services. Besides physical health problems, lack of contact with primary care may preclude the identification and delivery of appropriate interventions. We examined health service utilization in the longitudinal Boricua Youth Study of Puerto Rican children residing in the South Bronx (SBx), New York City ( n = 901), and San Juan metropolitan area, Puerto Rico ( n = 1,163). Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Yet, it is currently unclear what role sex and child maltreatment subtype play in the development of sensation seeking across childhood and adolescence. Similarly, while research has demonstrated that prevalence rates of child maltreatment subtypes vary by sociocultural context (Feldman et al, 2010; Suglia et al, 2019), it is unclear if the relationship between child maltreatment subtypes, sex, and sensation seeking relates to sociocultural context.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it is currently unclear what role sex and child maltreatment subtype play in the development of sensation seeking across childhood and adolescence. Similarly, while research has demonstrated that prevalence rates of child maltreatment subtypes vary by sociocultural context (Feldman et al, 2010; Suglia et al, 2019), it is unclear if the relationship between child maltreatment subtypes, sex, and sensation seeking relates to sociocultural context.…”
Section: Introductionmentioning
confidence: 99%
“…Children use health services for diverse purposes, such as emergency treatment for injuries and assessment and treatment of illness. Vulnerable children, such as those experiencing maltreatment, may use health services, particularly emergency care frequently 1 . Patterns of health service utilization by these highly vulnerable children may provide insights into the prevalence of maltreatment nationally, as well as factors that may impact that prevalence, which could inform efforts to prevent child maltreatment and its associated consequences.…”
mentioning
confidence: 99%